Basic needs and rural development : part 1 seminar papers - Beg, M. A. K.; Anwer, S. M.; Azim, M. (Peshawar : Pakistan Academy for Rural Development, 1980)
"Paper I Seminar Papers" covers the "Seminar Papers" presented at the International Seminar on Basic Needs Strategy for Rural Development and International Workshop on Training on [sic] Rural development held in May 1979
papers presented at the International Seminar on Basic Needs Strategy for Rural Development and International Workshop on Training on [sic] Rural development held in May 1979
Includes bibliographical references and index.
rpm 10/11/2017
Loans
Keywords: Rural development; Basic needs